Fruit of the dead eaudiobook A novel. - Lyon, Rachel (Simon & Schuster Audio, 2024)
Named a Best Book of the Year by Oprah Daily * "Mesmerizing." — Town & Country * "Twisty and unsettling." — People * "Ancient Greece meets Succession by way of Emma Cline...deliciously dark." —Ruth Gilligan * A "superb...refreshing" ( The New York Times Book Review ) reimagining of the myth of Persephone and Demeter set on a lush private island, exploring themes of addiction and sex, family, independence, and who holds the power in a modern underworld. Camp counselor Cory Ansel, eighteen and aimless, afraid to face her high-strung single mother's disappointment, is no longer sure where home is when the father of one of her campers offers an alternative. The CEO of a pharmaceutical company, Rolo Picazo is wealthy, divorced, and magnetic. He is also intoxicated by Cory. When Rolo offers her a job, Cory quiets an internal warning and allows herself to be ferried to his private island. Plied with luxury and the opiates manufactured by his company, she tells herself she's in charge. Her mother, Emer, head of a teetering agricultural NGO, senses otherwise. With her daughter seemingly vanished, Emer crosses land and sea to heed a cry for help that only she can hear. Alternating between the two women's perspectives, Fruit of the Dead incorporates its mythic inspiration with a light touch and devastating precision. The result is a tale that explores love, control, obliteration, and America's late-capitalist mythos. Lyon's reinvention of Persephone and Demeter's story makes for a haunting, electric novel that readers will not soon forget.